An Investigation on the Impact of Consumer’s Individual Factors on Purchasing Fashion Items at Internet Vendors amongst Chinese Students in the UK - Wang, Yuhua (2011)
The aim of the dissertation is to develop managerial implications on the effective marketing strategies based on the suggestions made through the research based on the findings on the extent to which the impact of individual psychological factors on Chinese students’ purchase decision-making on fashion items at online fashion retailer in the UK. The research methods adopted for the dissertation is linear regression analysis which assists in determining the relationship of the variables. The findings based on the data analysis are that both PU and PEOU have a positive relationship with attitude to purchasing fashion clothing products at internet vendors. PEOU is relatively significant TAM factor influence consumer’s attitude comparing to PU. There is a significantly positive relationship between trust and PU. Payment security may have a slight positive relationship with consumer’s trust toward internet fashion vendors. Consumer’s enjoyment on the attributes of the website of the fashion vendors are related but insignificantly.